Paradigms in epistemic communities. An analysis of development studies seen from REEDES and EADI - Pinzón Moreno, Juliana A.; Iliana; Antonio (Papeles de Europa, 2024)
Based on the historical, social, and political role that epistemic communities play as means of production, circulation and legitimation of ideas, this research explores the evolution and current configuration adopted by paradigms in the discipline of development studies. To this end, two of its most consolidated epistemic communities, REEDES and EADI, have been taken as case studies and their academic conferences (carried out from 2010 to 2020) were analysed as they represent ideas and intentions of the community. The results of this paper indicate that, although they share certain patterns, there are important points of divergence, since the presence of different types of actors configures paradigms according with the needs, interests and social structures in which they develop.
Keywords: Economic development: general (O10); Development of the Discipline: Historiographical; Sources and Methods (N01); International Linkages to Development; Role of International Organizations (O19)